Victorian literature and finance - O'Gorman, Francis (Oxford University Press, 2007)
This edited work analyses relationships between writing and the financial structures of the 19th century. What emerges is a set of imaginative connections between literature and Victorian finance, including women and the culture of investment, the profits of a media age, and the relationship between literary and financial capital.